Enhancing performance in elite water polo players: Dry-land training, in-water training, and combined training - Ramos Veliz, R.; Suarez Arrones, L.; Requena, B.; Saez de Villarreal, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Objective: This study compares the effect of three different training stimuli on strength and other qualities critical to water polo (WP) performance. Design: Thirty elite WP players were randomly assigned to three experimental groups: combined training (dry-land and inwater strength training, CG), in-water specific strength (WSG), and plyometric (PG). Participants performed strength and plyometric training three days a week for a total of 6 weeks. WP training was conducted five days per week. Method: 10m-T-Agility Test, 20-m maximal sprint swim, maximal dynamic strength (1RM, bench press (BP) and full squat (FS), in-water vertical jump, countermovement jump (CMJ) and throwing velocity (ThV) were measured. Results: Pre-training results showed no significant differences among the groups in any of the variables tested. After six weeks significant improvements (p.0.05) were found in PG group in CMJ (6.1%); in CG and WSG groups inwater vertical jump (4.4%) and (5.1%), respectively. Maximal dynamic strength 1RM FS significantly increased in all groups ([CG (14.20%), WSG (11.55%), and PG (14.59%)]), but in 1RM BP increased only in the CG and PG groups (12.65%) (7.67%) respectively. ThV significantly increased in all groups ([CG (17.57%), WSG (12.80%), and PG (11.43%)]) and in Agility test only CG group (7.37%) significantly decreased. Conclusions: A combined training approach using dry-land and in-water specific strength exercises results in a improvement in maximal strength, in-water vertical jump, throwing and agility performance and the resemblance between movement patterns and the specificity of strength exercises common to the training and testing methods also contributes to greater performance improvement.